The Potential of Edu-Ecotourism 'Floradventure' in Djuanda Forest Park, Bandung - Fauziah, Abidah; Surakusumah, Wahyu; Polando, Chersy Tiffany; Fadhilah, Fathan; Abthal, Ok M. (Universitas Pendidikan Indonesia and Konsorsium Biologi Indonesia, 2024)
Ir. H. Djuanda Forest Park (Tahura) is a protected area of 526.98 hectares that functions as a protected forest and tourist attraction. With 85% local flora and 15% from other bioregions, Tahura provides research, education, and recreation facilities. The area is made up of secondary natural forest and plantation forest, serving as a natural laboratory with vegetation from 40 families and 112 species, including both native and exotic plants. This research aims to develop the educational tourism package